"Factors associated with provider unwillingness to perform induced abortion in Argentina: A cross-sectional study in four provinces following the legalization of abortion on request". - Paula Vázquez; Carolina Nigri; Verónica Pingray; Luz Gibbons; Sandra Formia; Analía Messina; Claudia Castro; Cintia Jacobi; Adriana Martiarena; Susana Velazco; Ana Langer; Jewel Gausman; et al. (PLoS ONE, 2023)
Background The 2020 Law on Access to the Voluntary Interruption of Pregnancy is a landmark piece of legislation regarding access to abortion in Argentina. Under the new law, abortion is legal up to 14 weeks and 6 days gestation, with exceptions made to the gestational age limit to save a woman´s life, to preserve a woman´s health, and in case of rape. However, widespread refusal to provide care by authorized health providers (due to conscientious objection or lack of awareness of the new law) could hinder access to legal abortion. This study aimed to assess knowledge of the current legal framework and willingness to perform abortions by authorized professionals in Argentina, to compare perceptions about any requirements necessary to perform abortions on legal grounds between willing and unwilling providers and to explore factors associated with refusal to provide care. Methods We conducted a cross-sectional study based on a self-administered, anonymous survey to authorized abortion providers in public health facilities in four provinces of Argentina. Findings Most authorized providers knew the grounds upon which it is currently legal to perform abortions; however, almost half reported being unwilling to perform abortions, mainly due to conscientious objection. Both willing and unwilling providers believed there were additional requirements not actually stipulated by law. Using logistic regression, we found that province where providers serve, working in a tertiary level facility, and older age were factors associated with unwillingness to provide care. Conclusions The results of our study indicate that, even in a favorable legal context, barriers at the provider level may hinder access to abortion in Argentina. They help to demonstrate the need for specific actions that can improve access such as training, further research and public policies that guarantee facilities have sufficient professionals willing to provide abortion care.